2013
DOI: 10.1038/ja.2013.4
|View full text |Cite
|
Sign up to set email alerts
|

Improved total synthesis of incednam

Abstract: An alternative and improved total synthesis of incednam, the aglycon of the 24-membered macrolactam glycoside antibiotic incednine, was accomplished. The synthesis was realized via construction of the 24-membered macrocycle using intramolecular ring-closing olefin metathesis reaction as a key step.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 22 publications
0
7
0
1
Order By: Relevance
“…With compounds 3a-d in our hands, a Mitsunobu reaction in the presence of diphenylphosphoryl azide (DPPA) was performed, [18] followed by a Staudinger reduction of the obtained azide. [19] In this way, the interconversion of compounds 3a-d into the corresponding amines (4a-d) was achieved with inversion of configuration. The amines were treated with acryloyl chloride (5a-d), affording the amides, which were converted into lactams (6a-d) through a ring-closing metathesis (RCM).…”
Section: Resultsmentioning
confidence: 99%
“…With compounds 3a-d in our hands, a Mitsunobu reaction in the presence of diphenylphosphoryl azide (DPPA) was performed, [18] followed by a Staudinger reduction of the obtained azide. [19] In this way, the interconversion of compounds 3a-d into the corresponding amines (4a-d) was achieved with inversion of configuration. The amines were treated with acryloyl chloride (5a-d), affording the amides, which were converted into lactams (6a-d) through a ring-closing metathesis (RCM).…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, we and others successfully utilized ring‐closing metathesis (RCM) reactions during the total synthesis of polyene macrocyclic natural products such as vicenistatin, FD‐891, and incednam . We therefore attempted to construct a 20‐membered polyene macrolactam skeleton by using RCM as shown in Scheme .…”
Section: Resultsmentioning
confidence: 99%
“…In previouss tudies, we and others successfully utilized ringclosing metathesis (RCM) reactions during the total synthesis of polyene macrocyclic naturalp roducts such as vicenistatin, [21] FD-891, [22] and incednam. [23] We therefore attempted to construct a2 0-membered polyenem acrolactams keleton by using RCM as shown in Scheme 6. The retrosynthetic disconnection between C10-C11 was chosen because 1) the RCM precursor would be easily accessible from our synthetic intermediate, and 2) we expected that C9-oxygen functionality of intermediate F could be used to modulate the reactivity of the vinyl group at C10, [24] which was sequesteredi nt he intramolecular pinacolcoupling reaction(see above).…”
Section: Total Synthesis Of the Reviseds Tructure Of Heronamide C: A mentioning
confidence: 99%
“…Theg roup from Keio University reported an improved total synthesis of incednam (2), the aglycon of the 24membered macrolactam glycoside antibiotic Incednine. [43] Theretrosynthetic analysis of 2 was based on the construction of the 24-membered macrocycle by ac hallenging intramolecular macrocyclization of the fragile polyunsaturated substrate 1 (Scheme 3). Conditions for the RCM were rigorously explored, such as screening of anumber of catalysts,including first-and second-generation Grubbs and Hoveyda-Grubbs catalysts,a sw ell as nitro catalyst Ru12.T hese tests revealed that the best conditions consist of using Ru12 in the presence of p-methoxyphenol (PMP) [44] and 3 molecular sieves.…”
Section: Examples In Ring-closing Metathesismentioning
confidence: 99%